2020
DOI: 10.1055/a-1265-7209
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Imaging in Patients with COVID-19 and Neurological Symptoms: First Experience from two University Hospitals in Northern Germany

Abstract: Purpose To describe findings on cerebral imaging in patients with COVID-19 and neurological symptoms at two German university hospitals. Materials and Methods Patients with COVID-19 and neurological symptoms and cerebral imaging (CT or MRI) were included. A chart review regarding neurological symptoms, COVID-19 and imaging findings was conducted. Results 12 patients (4 females, age 68 ± 12 years) could be included. Three patients had acute findings. Two patients had acute and subacute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…442 patients (188 females, 42.5%) were included. Some of the patients have already been partially described in previous publications [ 6 8 ]. Mean age was 69 ± 16 years (range 19–99).…”
Section: Resultsmentioning
confidence: 99%
“…442 patients (188 females, 42.5%) were included. Some of the patients have already been partially described in previous publications [ 6 8 ]. Mean age was 69 ± 16 years (range 19–99).…”
Section: Resultsmentioning
confidence: 99%
“…Regional brain alterations appear to persist postinfection [ 37 , 69 , 78 , 85 , 111 ]. For example, Sollini et al.…”
Section: Resultsmentioning
confidence: 99%
“…Ischemic stroke (11.9%) was the most common acute finding. Several hypotheses suggested that the pathogenesis of stroke in COVID-19 may be attributed to the development of coagulopathy or endothelial dysfunction [ 9 , 14 ]. Systemic inflammation and cytokine storm triggers the coagulation system with subsequent development of a hypercoagulable state.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that SARS-CoV-2 shows a high affinity for the angiotensin-converting enzyme 2 (ACE2) receptor, which is expressed in the epithelium of the upper and lower airways, as well as the endothelium of the capillaries including those in the central nervous system [ 14 ]. At the same time, COVID-19 patients, especially severe cases, frequently present severe systemic manifestations such as viremia, hypoxia, cytokine storm, and coagulopathy.…”
Section: Introductionmentioning
confidence: 99%